Aplikasi Mobile Augmented Reality untuk Pengenalan Tata Surya sebagai Media Pembelajaran - Aspin William Roy; Sri Wulandari (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Along with the rapid development of technology from year to year, more and more learning methods are being created to support the teaching and learning process. Learning media in the form of solar system learning aids still use print media, video tutorials, and teaching aids and are still relatively simple, in which the teacher is more dominant in explaining and explaining, and students only listen and listen to the teacher's explanation. Another reason is the limited use of solar system props. On the other hand, there is the latest technology that can be developed into learning media. The application of Augmented reality in solar system learning media aims to provide innovative learning methods that are believed to create interesting learning for students because they are packaged as attractively as possible using 3D image displays, which make the appearance of objects look more real so that this can encourage student learning interest.